2012
DOI: 10.1021/jm300926y
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Conformationally Constrained Cyclopentapeptide Antagonists for C-X-C Chemokine Receptor 4 (CXCR4)

Abstract: In the absence of an experimentally determined binding mode for the cyclopentapeptide CXCR4 antagonists, we have rationally designed conformationally constrained analogues to further probe the small peptide binding pocket of CXCR4. Two different rigidification strategies were employed, both resulting in highly potent ligands (9 and 13). The information provided by this cyclopentapeptide ligand series will be very valuable in the development of novel peptidomimetic CXCR4 antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 30 publications
(86 reference statements)
0
40
0
Order By: Relevance
“…Extensive SAR studies of FC131 involving more conservative side chain modifications have been performed, and due to the large number of analogs, we only summarize the main findings. § Arg 1 is relatively tolerant to a range of structural modifications, indicating that it participates in non--specific receptor interactions [88,96,97]. § Arg 2 is very sensitive to the same modifications, indicating that it is involved in highly specific receptor interactions [97,98].…”
Section: Side Chain Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive SAR studies of FC131 involving more conservative side chain modifications have been performed, and due to the large number of analogs, we only summarize the main findings. § Arg 1 is relatively tolerant to a range of structural modifications, indicating that it participates in non--specific receptor interactions [88,96,97]. § Arg 2 is very sensitive to the same modifications, indicating that it is involved in highly specific receptor interactions [97,98].…”
Section: Side Chain Modificationsmentioning
confidence: 99%
“…§ Arg 1 is relatively tolerant to a range of structural modifications, indicating that it participates in non--specific receptor interactions [88,96,97]. § Arg 2 is very sensitive to the same modifications, indicating that it is involved in highly specific receptor interactions [97,98]. § 2--Nal 3 is also sensitive to modifications, and the distal aromatic ring has been shown to be especially important [98,99].…”
Section: Side Chain Modificationsmentioning
confidence: 99%
“…As SAR studies of the cyclopentapeptide CXCR4 antagonists (Figure 1) have demonstrated that position 2 (L-Arg) is very sensitive to structural modifications, 12,13 we decided to keep LArg 2 throughout this study. Similarly, we have recently shown that replacement of L-2-Nal in position 3 with aromatic/alicyclic analogs results in significant reduction of the antagonistic potency, 11 and therefore used a 2-naphthyl group with the appropriate spacer length for all compounds.…”
Section: General Design Considerationsmentioning
confidence: 99%
“…The antagonistic potency of the synthesized compounds 2-14 ( Figures 2 and 6) on human CXCR4 was determined by a functional assay as previously described 13 and is shown in Table 1; the EC 50 -value of the known lead compound 2 was 0.52 µM. …”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation